2017
DOI: 10.5489/cuaj.3789
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid urothelial carcinoma (PUC): Imaging features with histopathological correlation

Abstract: Cite as: Can Urol Assoc J 2017;11(1-2):E50-7. http://dx.doi.org/10.5489/cuaj.3789 Published online January 12, 2017 AbstractIntroduction: Plasmacytoid urothelial carcinoma (PUC) is a highgrade variant of conventional urothelial cell carcinoma. This study is the first to describe the imaging findings of PUC, which are previously unreported, using clinical and histopathological correlation. Methods: With internal review board approval, we identified 22 consecutive patients with PUC from 2007-2014. Clinical param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…15 Pelvic peritoneal infiltration by PUC can be detected on radiology as thick sheets extending along the fascial planes and is suggested to be a characteristic imaging finding. 23 On follow-up, PUC has an aggressive course, with high recurrence rates. 8,9,11,[13][14][15] In the largest series of 98 PUCs from Memorial Sloan Kettering Cancer Center, the median overall survival was reported to be 3.8 years, 4.1 years shorter than in matched conventional urothelial carcinoma (8 years).…”
mentioning
confidence: 99%
“…15 Pelvic peritoneal infiltration by PUC can be detected on radiology as thick sheets extending along the fascial planes and is suggested to be a characteristic imaging finding. 23 On follow-up, PUC has an aggressive course, with high recurrence rates. 8,9,11,[13][14][15] In the largest series of 98 PUCs from Memorial Sloan Kettering Cancer Center, the median overall survival was reported to be 3.8 years, 4.1 years shorter than in matched conventional urothelial carcinoma (8 years).…”
mentioning
confidence: 99%
“…20,21,26,27 Recently, GATA3 has shown to be of value in UC, including PUC. 3,22 Zhao et al reported high specificity of GATA3 as a diagnostic marker in PUC, showing a higher expression in regional metastasis. 28 Therefore, GATA3 seems to be an appropriate marker for differential diagnosis, useful in recognizing the urothelial lineage of PUC in metastatic patients.…”
Section: Discussion Diagnosismentioning
confidence: 99%
“…Recently, imaging findings of PUC have been described resembling histological spread of tumor with invasive T 2 W hypointense sheets of soft tissue extending from the primary tumor and spreading along fascial planes with restricted diffusion (Fig. ) . A propensity for locally recurrent disease and peritoneal metastases has also been described in PUC .…”
Section: Bladder Cancer Variantsmentioning
confidence: 96%
“…7). 79 A propensity for locally recurrent disease and peritoneal metastases has also been described in PUC. 80 Imaging features of micropapillary and sarcomatoid variants have not, to our knowledge, been described in the imaging literature.…”
Section: Bladder Cancer Variantsmentioning
confidence: 99%